Experimental Study on the Road Performance of High Content of Phosphogypsum in the Lime–Fly Ash Mixture - Qian, Guoping; Zhong, Yixiong; Li, Xi; Peng, Huaizhi; Su, Ju; Huang, Zichao (Frontiers in Materials, 2022)
Phosphogypsum (PG), as a by-product of the production of phosphoric acid, faces the problems of large annual output and difficult treatment. There is a large demand for fillers in the process of road paving, which may be an effective method for the utilization of PG resources. In this paper, three proportions of phosphogypsum-lime-fly ash (PLF) mixture were designed firstly according to orthogonal tests. The comprehensive performance of the PLF mixture was tested by compression rebound modulus test, unconfined compressive strength test, flexural tensile strength test, dry shrinkage test and temperature shrinkage test, respectively. The results show that adding crushed stone to the PLF mixture can effectively improve the compression rebound modulus, unconfined compressive strength and flexural tensile strength. The high content of PG in the mixture can also improve the dry shrinkage and temperature shrinkage properties of the mixture. According to the road layer requirements, the optimum proportion of the PLF mixture is recommended, which may benefit the road construction and PG resourced.